Buffering the service failure-induced effect of anger on revenge. Issue 7 (10th June 2019) - Walsh, Gianfranco; Deseniss, Alexander; Ivens, Stefan; Schaarschmidt, Mario
Abstract : Purpose: This paper aims to increase understanding of how the strength of the relationship between service failure-induced customer anger and revenge intentions might be influenced by attitudinal moderators that are both within and outside the realm of the service firm's control. Drawing on past research, the authors hypothesize that customers' perceptions of the corporate reputation and silent endurance constitute boundary conditions of the relationship between service failure-related customer anger and revenge intentions. Design/methodology/approach: In line with past service failure research, the authors test the hypotheses using a scenario-based online experiment with 243 participants. Findings: This research reaffirms the positive relationship between anger and revenge intentions and finds support for the hypothesized boundary conditions; customers with better corporate reputation perceptions and higher levels of silent endurance express weaker revenge intentions than those with poor corporate reputation perceptions and lower levels of silent endurance. Originality/value: This research offers unique insights into how service organizations can buffer the detrimental effects of service failure-induced customer anger.